Impact Evaluation of the Multi-Grade Classroom Readiness Program for Prospective Teachers: The First Step to Villages Schools (FSVS) Program: Arzu ŞAHİN, Ramazan SAĞ, Ferat YILMAZ, Ayça KARTAL, Gökçen KARAMAN - . (PJDOL, 2022)
This study aims to evaluate the effectiveness of the online version of the First Step to Village Schools (FSVS) Program in Turkey, which seeks to fill the knowledge and practice gap of prospective teachers, via mixedmethods research. Participants were volunteer university students from various faculties of education. In the quantitative part of the study, a single group pre-test/post-test design was used. Researchers developed the Rural School Teaching and Communication scale (KOIO), the Professional Knowledge and Skills scale (MBBO) and the Personal-Interpersonal Skills scale (KSBO). The SPSS program was used to analyze the quantitative data. During the qualitative data collection, prospective teachers were asked 3 open-ended questions as part of the post-test and a phenomenological design was used. The inductive content analysis technique was used for the analysis of the qualitative data. The results show that the FSVS program contributed to teacher candidates’ development in professional knowledge and skills and individual-social skills such as teaching and communication in rural areas. The experience of prospective teachers achieved during the FSVS program is interpreted as a transition from a lack of readiness to a state of readiness to teach in a village.